“From a certain angle”: ecothriller reading and science fiction reading "The Swarm" and "The Rapture" - Otto, Eric C. (Universidad de Alcalá, 2012)
Read as apocalyptic ecothrillers, Frank Schätzing’s The Swarm and Liz Jensen’s The Rapture do not offer much in the way of critical reflection on the ecocatastrophes they stage. The Swarm’s focus on the feat of confronting the violent efforts of a superintelligent, deep-sea species to protect its ocean habitat against continued human exploitation and The Rapture’s focus on the feat of locating on time the psychically-predicted disaster zone of an impending undersea calamity overshadow their more than occasional spotlighting of, for example, the dangers of methane hydrate mining. Science fiction, however, requires readers to be attentive to those narrative moments when incongruities between the known world and the extrapolated world of the text emerge with critical, not just plot-supporting, purpose. Fundamental to the reading and interpretation of science fiction is the reader’s awareness of the genre’s extrapolative practice, which connects the now with the imagined then and therefore instigates critical thinking about present human practices. Read as extrapolative science fiction, The Swarm and The Rapture gain merit as ecopolitical works, for “science fiction reading” mobilizes the latent ecopolitics of ecothrillers, ecopolitics that “ecothriller reading” would otherwise diminish or fail to notice. Considerados ecothrillers apocalípticos, The Swarm de Frank Schätzing y The Rapture de Liz Jensen no ofrecen mucha reflexión crítica sobre las eco-catástrofes que presentan. The Swarm se centra en los violentos esfuerzos de una especie superinteligente que habita las profundidades para proteger su hábitat marino frente a la continua explotación humana. Por su parte, al centrarse The Rapture en la hazaña de ubicar en el tiempo la zona catastrófica de un desastre submarino inminente que ha sido predicho psicológicamente, se eclipsan las más que ocasionales referencias a, por ejemplo, los peligros de la minería de hidrato de metano. La ciencia ficción, sin embargo, requiere que los lectores estén atentos a esos ...